Stimulation of α7 Nicotinic Acetylcholine Receptor by Nicotine Suppresses Decidual M1 Macrophage Polarization Against Inflammation in Lipopolysaccharide-Induced Preeclampsia-Like Mouse Model - Han, Xinjia; Li, Wei; Li, Ping; Zheng, Zheng; Lin, Baohua; Zhou, Bei; Guo, Kaimin; He, Ping; Yang, Jinying (Frontiers in Immunology, 2021)
Changes in decidual macrophage polarization affect local inflammatory microenvironment and lead to adverse pregnancy outcomes. However, the regulatory mechanism of macrophage polarization in preeclampsia (PE) remains unclear. We previously found that nicotine which was an agonist for α7 nicotinic acetylcholine receptor (α7nAChR) could alleviate systemic inflammation and preeclampsia-like symptoms. Here, we investigated the regulatory role of α7nAChR activation by nicotine on decidual macrophage polarization and placental remodeling in the PE-like mouse model. The PE mice were obtained by i.p. injection of 10 µg /kg lipopolysaccharide (LPS) gestational day (GD) 13, and 40 µg /kg LPS daily until GD16. Subcutaneous injection of 1.0 mg/kg nicotine was administrated from GD14 to GD18. Nicotine treatment increased the decreased M2 phenotype and inhibited the increased M1 phenotype in decidua of pregnant mice induced by LPS. The levels of pro-inflammatory cytokines in decidua were higher but the levels of anti-inflammatory cytokines were lower in PE mice compared to the controls, nicotine reversed these changes. The α7nAChR activity on decidual macrophages became decreased in PE patients compared to normal pregnancies. The level of choline acetyltransferase (CHAT) was reduced in the LPS-treated group, it was increased following nicotine treatment. Damage of spiral artery remodeling and down-regulation of markers related to trophoblast invasion in placentas were found in PE mice; nicotine improved these pathological structures of placentas. α-bungarotoxin (α-BGT) which is specific antagonist for α7nAChR could abolish the effects of nicotine on decidual macrophage polarization, trophoblast arrangement and vascular structure in placental tissue in PE mice. These results suggest that α7nAChR plays an important regulatory role in maternal-fetal inflammation and placental remodeling in preeclampsia and may provide a theoretical basis for the discovery of new strategies for preeclampsia.